Multi-Concept Frailty Predicts the Late-Life Occurrence of Cognitive Decline or Dementia: An Updated Systematic Review and Meta-Analysis of Longitudinal Studies - Guo, Chun-Yan; Sun, Zhen; Tan, Chen-Chen; Tan, Lan; Xu, Wei (Frontiers in Aging Neuroscience, 2022)
Background Frailty is a multidimensional syndrome that increases an individual’s vulnerability for developing adverse health outcomes, which include dementia. It might serve as a promising target for dementia prevention. However, there are currently no studies summarizing the association between multi-concept frailty and the risk of cognitive disorders. This study aims to summarize the evidence of associations between multi-concept frailty and cognitive disorders based on longitudinal studies. Methods Scopus, The Cochrane Library, PsycINFO, CINAHL, PubMed, and EMBASE databases were searched from inception to January 2, 2022. Longitudinal studies, which explored the association of frailty with incident risk of cognitive decline or dementia, were included. The multivariable-adjusted effect estimates were pooled by random-effects models. The evidence credibility was depicted according to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method. Results A total of 30 longitudinal studies were included. Four types of frailty concepts were involved, including physical, cognitive, social, and biopsychosocial frailty. The meta-analysis comprised 20 studies of 252,571 older adults (mean age: 64.1–80.4 years), among whom 7,388 participants developed cognitive decline or dementia. Physical frailty was associated with higher risk of developing cognitive disorders [pooled relative risk (pRR) = 1.52, 95% confidence interval (CI): 1.28–1.80, I2 = 21.2%, pRR = 1.62 for cognitive decline, 95% CI: 1.07–2.45, I2 = 40.2%, pRR = 1.37 for all-cause dementia (ACD), 95% CI: 1.13–1.66, I2 = 0.0%]. Cognitive frailty (pRR = 2.90, 95% CI: 1.28–6.55, I2 = 78.1%) and pre-frailty (pRR = 4.24, 95% CI: 2.74–6.56, I2 = 30.2%) were linked to higher risk of ACD. Biopsychosocial frailty could predict a 41% (pRR = 1.41, 95% CI: 1.17–1.71) elevated risk of cognitive decline or dementia [pRR = 1.53 (95% CI: 1.19–1.96) for ACD and 1.11 (95% CI: 1.05–1.17) for Alzheimer’s disease (AD)]. In the systematic review, social frailty was associated with a 53% higher risk of AD. Preventing frailty could avoid a maximum of 9.9% cognitive disorders globally. The overall evidence strength is rated as low-to-moderate. Inconsistency and imprecision are major sources of bias. Conclusion Frailty in late life is a promising risk factor for cognitive disorders. Frail elderly should be monitored for their cognitive dynamics and initiate early prevention of dementia. Systematic Review Registration www.ClinicalTrials.gov, identifier CRD4202127 3434.